The Impact of Accountability and Transparency of Government Financial Reports on the Achievement of SDGs 2 in Indonesia - Fitria Ramadhani; Muhammad Iqbal; Jurana Jurana; Rudy Usman (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the influence of accountability and transparency in government financial reports on the achievement of Sustainable Development Goals (SDGs) 2 in Indonesia. SDGs 2 focuses on efforts to eradicate hunger, increase food security, and improve public nutrition. The study used a quantitative approach with panel data in 34 provinces in Indonesia during the 2021–2022 period. The sampling technique was purposive sampling, resulting in a total of 68 research observations. The research data were sourced from the National Development Planning Agency (BAPPENAS), the Supreme Audit Agency (BPK), and official local government websites related to the publication of regional financial reports. The accountability variable was measured using the BPK audit opinion on the LKPD, while transparency was measured based on the openness of the publication of seven components of the regional government financial report. Data analysis was performed using the Common Effect Model (CEM) with a robust standard error approach. The results showed that accountability has a positive and significant effect on the achievement of SDGs 2 with a coefficient value of 3.919 and a significance level of 0.000. Transparency also has a positive and significant effect on the achievement of SDGs 2 with a coefficient value of 2.415 and a significance level of 0.000. In addition, accountability and transparency simultaneously proved to have a significant effect on the achievement of SDGs 2. This finding indicates that the implementation of good governance through increased accountability and transparency of financial reports can support the effectiveness of food security and sustainable development programs in Indonesia.